2022
DOI: 10.3389/fpubh.2022.858144
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Working Environment on Nurses' Caring Behavior in Sabah, Malaysia

Abstract: AimsThis study aims to investigate 5 types of work environment influencing nurses' caring behavior, namely (i) participation in hospital affairs, (ii) foundations for quality of care, (iii) manager ability, leadership, and support of nurses, (iv) staffing and resource adequacy, and (v) nurse-physician relations.DesignThis research is a cross-sectional study using the survey method.MethodsData were collected from 3,532 nurses working in public hospitals and health clinics within Sabah, Malaysia in 2015. The hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Nurses and midwives with a higher level of doctor-nurse/midwife relationships were 5.1 times more likely to have a higher perception of caring behaviors than those with a relatively poor level of doctor-nurse/midwife relationships. This finding was supported by studies conducted in various parts of Ethiopia [ 14 , 16 , 17 , 24 ], and Malaysia [ 42 ]. The reason for this could be that better relationships between physicians and nurses-midwives help to create a positive environment and a sense of autonomy for nurses and midwives, allowing them to demonstrate good caring behavior.…”
Section: Discussionsupporting
confidence: 72%
“…Nurses and midwives with a higher level of doctor-nurse/midwife relationships were 5.1 times more likely to have a higher perception of caring behaviors than those with a relatively poor level of doctor-nurse/midwife relationships. This finding was supported by studies conducted in various parts of Ethiopia [ 14 , 16 , 17 , 24 ], and Malaysia [ 42 ]. The reason for this could be that better relationships between physicians and nurses-midwives help to create a positive environment and a sense of autonomy for nurses and midwives, allowing them to demonstrate good caring behavior.…”
Section: Discussionsupporting
confidence: 72%
“…However, our finding revealed insignificant difference between both groups of nurses. Only two recent studies were found that addressed this variable [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on caring behaviours mainly focused on the impact of the care delivery system, workplace climate, values, and cultural background [ 8 , 9 ]. However, psycho-emotional aspects caring might be negatively affected with the continuous advancement in ICU technology, engagement of artificial intelligence, and increasing digitization in ICU care, for example, tele-ICU [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing care behavior is defined as an act, behavior, and mannerism by professional nurses that convey concern, safety, and attention to the patient [4]. Professional nursing practices are implemented through direct and indirect nursing care [5]. Direct nursing care is the most prioritized in nursing practice and can be observed in nurses' behavior, quality of nursing care, and patient outcomes care [5].…”
Section: Introductionmentioning
confidence: 99%